THU0105 Prediction of response to CERTOLIZUMAB-PEGOL in rheumatoid arthritis (PRECEPRA) by functional MRI of the brain – an interim analysis of an ongoing investigator initiated phase III trial. (15th June 2017) - Schenker, H; Hess, A; Konerth, L; Sergeeva, M; Prade, J; Kleyer, A; Reiser, M; Hueber, A; Englbrecht, M; Feist, E; Voll, RE; Bannert, B; et al.
Abstract : Background: Tumor necrosis factor inhibitors (TNFi) signify a major advance in the treatment of rheumatoid arthritis (RA). However, treatment success initially remains uncertain as one third of patients do not respond adequately to TNFi. Objectives: We investigated whether brain activity associated to arthritis measured by functional magnetic resonance imaging (fMRI) can function as a predictor of response to TNFiin RA patients. Methods: This is an interim analysis of the first 50 patients of the PreCePRA trial, a multi-center, double-blind, placebo-controlled fMRI trial on patients with RA. [1] [2] Active RA patients failing csDMARDs with a DAS28-ESR >3.2 and at least three tender and/or swollen joints received a baseline brain BOLD fMRI scan upon joint compression at screening. Patients werethen randomized into a 12-week double-blinded treatment phase with placebo (arm 1) or 200mg certolizumab-pegol eow (arm 2; fMRI Bold signal>2000 voxel i.e. 2cm 3, arm 3; fMRI Bold signal <2000 voxel). LDA 3mo. Primary end point was DAS28-ESR low disease activity at 12 weeks. A 12 weeks follow-up phase in which patients were switched from the placebo to the treatment arm folowed the blinded phase. fMRIwas carried out at baseline as well as after 12 and 24 weeks of or placebo. Results: In 31 patients (responders) baseline signal volume i.e. sum of significantly coupled voxels after the FDR thresholding was significatly higher compared to 19 patients (non-responders) (p<0.001) allowing discrimination between the two groups prior to treatment. In responders we detected an persitent decrease of the BOLD volume from baseline to week 12 and week 24 (r 2 =0.561) whereas the BOLD volume in non-responders persitently increased (r 2 =0.589). Conclusions: Based on this interim analysis we conclude that high BOLD volumes in fMRI, indicating high-level brain representation of pain in arthritis. These data represent the first encouring signal of the PreCePRA brain fMRI study supporting the concept that increased RA-related brain activity is related to response to TNFi. References: Rech, J., et al., Association of brain functional magnetic resonance activity with response to tumor necrosis factor inhibition in rheumatoid arthritis. Arthritis Rheum, 2013.65(2): p. 325–33. Hess, A., et al., Blockade of TNF-alpha rapidly inhibits pain responses in the central nervous system. Proc Natl Acad Sci U S A, 2011.108(9): p. 3731–6. Disclosure of Interest: None declared